Non-REM Sleep Characteristics Predict Early Cognitive Impairment in an Aging Population - Taillard, Jacques; Sagaspe, Patricia; Berthomier, Christian; Brandewinder, Marie; Amieva, Hélène; Dartigues, Jean-François; Rainfray, Muriel; Harston, Sandrine; Micoulaud-Franchi, Jean-Arthur; Philip, Pierre (Frontiers in Neurology, 2019)
Objective Recent studies suggest that sleep disorders or modifications of sleep stages or EEG waveform precede over the years the onset of clinical signs of pathological cognitive impairment (e.g., Alzheimer's disease). The aim of this study is to identify biomarkers based on EEG power values and spindles characteristics during sleep that occur early in mild cognitive impairment in older adults. Methods This study is a case-control cross-sectional study and one-year follow-up of the cases. Patients with isolated subjective cognitive complaints or mild cognitive impairment were recruited in Memory Clinic of Bordeaux (MEMENTO cohort). Cognitively normal controls were recruited. All participants were recorded with two successive polysomnography recordings one year apart. Delta, theta and sigma absolute spectral power and spindle characteristics (density, amplitude and frequency) were computed from purified CzOz EEG derivation during NREM sleep periods (ASEEGA software) across the whole second night. Results Twenty-nine patients (21 females, age=71 years ±7) and 29 controls were evaluated at T0. Logistic regression analyses showed that a reduced delta power (odds ratio (OR) 0.996, P<.05), theta power (OR 0.950, P<.05), sigma power (OR 0.662, P<.05), and spindle maximal amplitude (OR 0.728, P<.05) during NREM sleep periods were associated with cognitive impairment in aging. Variables were adjusted on age, gender, Body Mass Index, educational level and medication use. Seventeen patients were evaluated at one-year follow-up. Correlations showed that changes in self-reported sleep complaints, sleep consolidation and spindle characteristics (spectral power, maximal amplitude, duration and frequency) were associated with cognitive impairment (P<.05). Conclusion A reduction in slow-wave, theta and sigma activities, and a modification of spindle characteristics during NREM sleep, are associated very early with a higher risk of occurrence of cognitive impairment. Poor sleep consolidation, lower amplitude and faster frequency of spindles may be potentially early sleep biomarkers of worsening cognitive decline in older adults.